2018
DOI: 10.1248/bpb.b18-00064
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzoylmethane, a Component of Licorice, Suppresses Monocyte-to-Macrophage Differentiation and Inflammatory Responses in Human Monocytes and Mouse Macrophages

Abstract: The objective of this study was to investigate the effect of dibenzoylmethane (DBM) on monocyte-to-macrophage differentiation, the inflammatory response, and the resulting signaling in human monocytes and murine macrophage. DBM effectively inhibited the monocyte-to-macrophage differentiation induced by phorbol 12-myristate 13-acetate (PMA) through a reduction in adhesion of THP-1 cells. Cluster of differentiation molecule β (CD11β) and CD36, which are surface markers of macrophage differentiation, were downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…RAW264.7 cells (5.0 × 10 5 cells per well) were seeded into six‐well plates. They were treated with PCG for 2 h, after which the medium was replaced with ACM and the cells were cultured for a further 24 h. Nitric oxide (NO) was examined as previously described …”
Section: Methodsmentioning
confidence: 99%
“…RAW264.7 cells (5.0 × 10 5 cells per well) were seeded into six‐well plates. They were treated with PCG for 2 h, after which the medium was replaced with ACM and the cells were cultured for a further 24 h. Nitric oxide (NO) was examined as previously described …”
Section: Methodsmentioning
confidence: 99%
“…RGE-mediated activation and suppression of Nrf2 and NF-jB, respectively, on the translocation into nucleus was shown to be interplayed for anti-inflammation (Wardyn et al, 2015). A recent study showed that the interaction of NF-jB and its target genes for inflammatory responses was interrupted by the Nrf2 activation (Kang et al, 2018). In reality, p-65, a NF-jB subunit, and Nrf2 were shown to compete for binding to transcriptional co-activator CREB-binding protein (CBP)-p300 complex (Sun et al, 2009).…”
Section: Effect Of Rge On Inflammatory Cytokinesmentioning
confidence: 99%
“…It moves into the nucleus, binds to promoter regions of inflammatory genes, and stimulates their expression, promoting inflammatory responses (Lee et al, 2008;Sung et al, 2012). In recent years, nuclear factor E2-related factor 2 (Nrf2) signaling, an antioxidant machinery, has also been implicated to inflammation (Kang et al, 2018;Kobayashi et al, 2016). The up-regulation of Nrf2 and its target gene, hemeoxygenase-1 (HO-1), a ratelimiting enzyme in heme catabolism, has been known to have cytoprotective effect, and suppress the inflammatory responses (Kobayashi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%